Clinical Evaluation of LASEK for High Myopia Correction between the Triple-A Profile and the Zyoptix Tissue Saving Profile - Min Li; Yuehui Shi; Lina Sun; Lin Liu; Chen Qu; Jun Zou (Journal of Ophthalmology)
Purpose. To compare the effects of correcting high myopia using the MEL®90 Triple-A profile LASEK at a 500 Hz pulse rate (Triple-A group) versus the Zyoptix tissue-saving ablations of Technolas 217z laser platform at 100 Hz (TS group). Methods. This retrospective study included 50 eyes in the Triple-A group and 42 eyes in the TS group with manifest refraction spherical equivalent (MRSE) of −6 diopters (D) to −10 D. We compared uncorrected distance visual acuity, MRSE, corrected distance visual acuity, and postoperative complications at 1 month, 3 months, and 6 months. Results. At 6 months after refractive surgery, the efficacy index of Triple-A group was significantly higher than that of the TS group (1.03 ± 0.12 vs 1.00 ± 0.11, P=0.04). The MRSE postoperatively in the Triple-A group was significantly lower than that in the TS group (0.25 ± 0.18 vs 0.38 ± 0.23, P<0.01). The safety indices in the two groups were almost the same after 6 months of surgery (1.03 ± 0.07 vs 1.04 ± 0.11, P=0.63). The proportion of eyes which achieved ±0.13 D was significantly higher in the Triple-A group than that in the TS group at 1 month (80% vs 59.5%, P=0.03), 3 months (82% vs 61.9%, P=0.03) and 6 months (84% vs 64.3%, P=0.03). The changes in refraction 6 months after surgery comparing with 1 month after surgery were 0.12 ± 0.10 D in the Triple-A group and 0.13 ± 0.08 D in the TS group (P=0.56). All (100%) of the patients in the Triple-A group and 50% of the patients in the TS group had a UDVA of 20/16 at 6 months after surgery (P<0.01). The induced spherical aberrations and total HOAs in the Triple-A group were significantly lower than those in the TS group (0.17 ± 0.02 μm vs 0.23 ± 0.02 μm, P<0.01; 0.20 ± 0.04 μm vs 0.39 ± 0.03 μm, P<0.01) at 6 months after surgery. The mean reduced corneal thickness was 113.06 ± 10.5 μm in the Triple-A profile group and 121.43 ± 23.46 μm in the TS group (P=0.02). No patient in either group had haze and high intraocular pressure 6 months after surgery. Conclusion. For treatment of high-myopia patients, the Triple-A profile was more effective, predictable, and accurate than the Zyoptix tissue-saving profile. Meanwhile, the Triple-A profile had less induced spherical aberrations, total HOAs, and cornea ablation depth than the Zyoptix tissue-saving profile. Patients in the Triple-A group with 500 Hz pulse rate treatment achieved superior results. The two surgical procedures were equivalent in terms of safety and stability.